Embroidered dual band textile antenna for ISM band application on bending performance - Vejasegaran, R. (Asian Research Publishing Network, 2016)
This research proposes a development of embroidered dual band textile antenna that could integrate wearable telecommunication device with a garment. The proposed antenna could operate at 2.4 GHz and 5.8 GHz of WLAN applications. Two versions of the presented antennas are developed from the conventional rectangular patch. Two types of slot structures are loaded on each antenna and the antenna performances are investigated. The research uses silver patted nylon and cotton wearable as conductive and nonconductive materials. Both antennas have successfully achieved reflection coefficient of less than -10dB at the targeted bands. Besides that, the antennas have directional pattern with a gain of more than 2.5dBi. Moreover, antenna performances on bending conditions of 20°, 30°, 40°, 50°, 60°, 70° and 80° have been carried out in simulation in terms of the reflection coefficient. The proposed antenna could be potential for closed point to point communication such as wireless power transfer for pacemaker application.